Cancer beliefs, risk perceptions, and health protective behaviors among people living with diabetes in the United States: Results from the Health Information National Trends Survey - Jiamin Hu; Young-Rock Hong; Daniela Rivero-Mendoza; William T. Donahoo; Naykky Singh Ospina; Stephanie A. Staras; Elizabeth Shenkman; Rahma S. Mkuu (Preventive Medicine Reports)
Objective: Diabetes and cancer share common preventable risk factors, including obesity, physical inactivity, and poor diet. People with diabetes have an increased risk of developing cancer. The objective of our study was to compare cancer risk perceptions, beliefs about cancer, and cancer protective behaviors among people with and without diabetes in the United States. Methods: We utilized data from the cross-sectional nationally representative Health Information National Trends Survey (HINTS) 6 (2022). Diabetes and cancer history were self-reported. We compared beliefs about cancer and cancer protective behaviors between individuals with and without diabetes who reported no cancer history. Results: The sample included 3937 individuals. There was no significant difference in beliefs about cancer (worry, risk, preventability, fatality, or prevention progress) and cancer protective behaviors (smoking, drinking, physical activity, and cancer information seeking) between individuals with diabetes and those without diabetes after adjustment. Conclusions: Our findings highlight the need for further research to enhance understanding and improve awareness of cancer risk and protective behaviors among people living with diabetes.